Equações polinomiais e matrizes circulantes - Oliveira Júnior, Pedro Jerônimo Simões de (2015)
In this work we discuss the procedures for solving polynomials equations of degree n 4; n 2 N via circulant matrices, highlighting a new perspective to obtain the Cardano- Tartaglia formulae. This brings up a new look on connected subjects, including the elimination of the term of degree (n1) and the characterization of real polynomials with all real roots. The method is based on searching a circulant matrix whose characteristic polynomial is identical to the one with the same roots we desire to nd. This approach provides us a simple and uni ed method for all equations through degree four.